DAKWAH KULTURAL: DIALEKTIKA ISLAM DAN BUDAYA DALAM TRADISI BATATAMBA - Jamalie, Zulfa; rif'at, muhammad (Alhadharah: Jurnal Ilmu Dakwah, 2012)
Batatamba is a local wisdom that has unique characteristics that are passed from generation to generation. The focus of this research is batatambah ritual against magical diseases that are believed by Banjarese people to be caused by the spirits from the unseen world. The findings of this study indicate that there has been a dialectics between Islam and culture in the tradition of batatamba. Their acculturation is beneficial and there was no tension or harm in the process. Therefore, there is a harmony between the two; Islam gives color or spirit to the culture, while culture provides a wealth of understanding for the religion as can be observed from Banjarese people life